The effect of automatic generation control (AGC) implementation on the electrical power system - Samsurizal, Samsurizal; Afandi, Arif Nur; Sitanggan, Mario Martinus Land (Jurnal Penelitian Saintek, 2025)
To enhance system resilience and prevent widespread blackouts from potential disruptions, a structured scheme is needed to reduce the impact of such disturbances. One of PLN's breakthrough initiatives is the activation of Automatic Generation Control (AGC) in the Java-Madura-Bali electricity system. Since the existing Load Frequency Control (LFC) system at Tambak Lorok PLTGU has been inactive for some time, the plant was selected for AGC implementation. This system is managed automatically by the Java Control Center (JCC) Dispatcher through a SCADA control scheme. This study aims to examine the effect of AGC activation on power plant regulation by JCC Dispatchers and to compare the SCADA system performance at Tambak Lorok with that of other power plants. A quantitative method with a descriptive approach was used, relying on SCADA point-to-point testing and real-time load trials with JCC Dispatchers. The results showed that during real-time testing, the Java-Bali grid frequency remained between 50.154 Hz and 49.819 Hz. These findings confirm AGC's effectiveness and support its broader implementation as a reliable solution for maintaining frequency stability and addressing challenges posed by intermittent renewable energy sources.